"Nach te an rud an Ghaeilge?/Isn't Irish a warm thing?" Learning Irish language and song: an autoethnographic self-reflection. (2nd January 2022) - Mac Corraidh, Seán
ABSTRACT: As ever more languages fall silent because transmission to children ceases, language revitalization has emerged as a worldwide issue today. A relative dearth of documentation exists about how, at an individual level, revitalization leads to the cultural formation of regular new speakers. Using autoethnographic approaches, this paper provides such a personal language biography. It relates significant and critical incidents from my memories of the academic, personal and professional pathways followed in learning Irish as a second language and gaining access to and appreciation of, the unaccompanied style of singing called sean-nós . Self-observation, self-exploration, self-reflection, autobiography and memorization guided the research and writing of the article. Autoethnographic theory provided the means for a greater critical understanding of social and cultural contexts tied to institutions, places and people. Documentation came in the form of photographs, video and audio recordings, personal letters and my own autobiographic writing.